2019
DOI: 10.1111/zph.12655
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis E virus RNA in rats caught in pig farms from Northern Italy

Abstract: Hepatitis E virus (HEV) strains belonging to the Orthohepevirus genus are divided into four species (A–D). HEV strains included in the Orthohepevirus A species infect humans and several other mammals. Among them, the HEV‐3 and HEV‐4 genotypes are zoonotic and infect both humans and animals, of which, pigs and wild boar are the main reservoirs. Viruses belonging to the Orthohepevirus C species (HEV‐C) have been considered to infect rats of different species and carnivores. Recently, two studies reported the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…From fifteen states in the USA though, all HEV sequences from the 35 rat livers positive, were related to HEV-3a [90]. Rats and mice trapped around pig farms were positive for HEV-3 in spleens in one study, but are mostly only positive in their intestines [47,86,89] or found test negative for HEV-3 [88]. The low prevalence of HEV-3 in rodents around farms and detection of HEV-3 predominantly in intestines, supports the argument that rodents are only accidental hosts of HEV-3.…”
Section: Rodentsmentioning
confidence: 93%
See 1 more Smart Citation
“…From fifteen states in the USA though, all HEV sequences from the 35 rat livers positive, were related to HEV-3a [90]. Rats and mice trapped around pig farms were positive for HEV-3 in spleens in one study, but are mostly only positive in their intestines [47,86,89] or found test negative for HEV-3 [88]. The low prevalence of HEV-3 in rodents around farms and detection of HEV-3 predominantly in intestines, supports the argument that rodents are only accidental hosts of HEV-3.…”
Section: Rodentsmentioning
confidence: 93%
“…In rats, HEV-3 RNA has been found, as well as a novel HEV gt, first called 'rat HEV' and now known as HEV gt C1 (species Orthohepevirus C) [87]. The prevalence of both HEV gt's in rodents varies from 0 to 18% dependent on the species (mice, R. rattus or R. norvegicus rats), the location where the rodents are found and the type of samples collected [47,86,[88][89][90][91]. In a study with 63 rats from twelve European countries, all contained HEV gt C1 RNA in their livers [91].…”
Section: Rodentsmentioning
confidence: 99%
“…To date, the vast majority of Orthohepevirus C genomes have been identified in Norway rats, from countries including the USA, China, Germany, France, Denmark, Lithuania, England, Hungary, Austria, Switzerland, Italy, Spain, Greece, Belgium, the Czech Republic, and Vietnam, with all viral strains belonging to HEV-C1 [19,20,24,25,29,[36][37][38][39][40][41][42][43][44][45][46]. Orthohepevirus C genomes have been detected in numerous other members of the family Muridae: HEV-C1 from Rattus rattus (Black Rat) has been detected in Indonesia, China, Kenya, and 12 other European countries comprising Lithuania, Germany, Hungary, Denmark, Austria, Switzerland, France, Italy, Spain, Greece, Belgium, and the Czech Republic [29,30,32,41,47,48]; Rattus tanezumi (Oriental house rat) in Vietnam and China have also been reported to harbor the virus [26,36,44,49]; in China, HEV-C1 RNA has been detected in Rattus losea (Losea rat), Rattus flavipectus (Yellow-breasted rat), and Bandicota indica (Greater bandicoot rat) [25,43,44]; Apodemus chevrieri (Chevrier's field mouse) and Apodemus agrarius (Striped field mouse) were positive for Orthohepevirus C detection; however, these variants are phylogenetically divergent from known HEV-C1 or HEV-C2, and thus, cannot yet be classified [36,50].…”
Section: Detection Of Orthohepevirus C Genomesmentioning
confidence: 99%
“…This rat HEV is a genetically distant relative of other mammalian HEVs; it is about 55-60% sequence homologous to HEV genotypes 1-4, and is assigned to the genus Orthohepevirus C (7). In Europe, studies conducted on Norway rats and Black rats, reported the detection of HEV-C RNA with prevalence ranging between 0.3 and 27.2% (8)(9)(10)(11)(12)(13)(14)(15); HEV-C RNA was also frequently detected in Asia with prevalence ranging between 0.7 and 26.3% in rats (16-21), 1.9% in musk shrew (22) and between 1.5 and 7.8% in 2 US studies in rats (23,24). The virus isolated in musk shrew could infect nude mice (25).…”
Section: Introductionmentioning
confidence: 97%